Synergetic antimicrobial effect of chlorin e6 and hydrogen peroxide on multi-species biofilms. Issue 6 (3rd July 2021) - Nie, Min; Silva, Rodrigo Costa e; de Oliveira, Kleber Thiago; Bagnato, Vanderlei Salvador; de Souza Rastelli, Alessandra Nara; Crielaard, Wim; Yang, Jingmei; Deng, Dong Mei
Abstract: Antimicrobial photodynamic therapy (aPDT) has been considered as a potential alternative to antibiotics for the treatment of biofilm infections. There is evidence that an additional H2 O2 enhances the antimicrobial efficacy of aPDT. However, the minimum H2 O2 concentration to achieve this synergistic effect is unclear. A saliva-derived multi-species biofilm was treated with the photosensitizer chlorin e6 (Ce6, 50 µM), H2 O2 (0.3, 3.3, 33.3 mM), or their combination for 5 min, followed by no irradiation or irradiation at 15 J (cm 2 ) −1 (λ = 450 nm or 660 nm), with or without oxygen. Biofilm viability and metabolic activity were evaluated. The combination of 33.3 mM H2 O2 and Ce6-aPDT strongly enhanced antimicrobial efficacy compared with either component alone, irrespective of oxygen availability and irradiation wavelength. In particular, the combination resulted in a 6.6-log colony forming unit (CFU) reduction anaerobically under blue irradiation. This combination is a promising treatment for biofilm infections, especially those thriving in an anaerobic microenvironment.